A Longitudinal Relationship Between Depressive Symptoms and Development of Metabolic Syndrome: The Coronary Artery Risk Development in Young Adults Study. Issue 7 (September 2016) - Womack, Veronica Y.; De Chavez, Peter John; Albrecht, Sandra S.; Durant, Nefertiti; Loucks, Eric B.; Puterman, Eli; Redmond, Nicole; Siddique, Juned; Williams, David R.; Carnethon, Mercedes R.
ABSTRACT: Objective: Despite variability in the burden of elevated depressive symptoms by sex and race and differences in the incidence of metabolic syndrome, few prior studies describe the longitudinal association of depressive symptoms with metabolic syndrome in a diverse cohort. We tested whether baseline and time-varying depressive symptoms were associated with metabolic syndrome incidence in black and white men and women from the Coronary Artery Risk Development in Young Adults study. Methods: Participants reported depressive symptoms using the Center for Epidemiologic Studies Depression Scale at four examinations between 1995 and 2010. At those same examinations, metabolic syndrome was determined. Cox proportional hazards models were used to examine the associations of depressive symptoms on the development of metabolic syndrome in 3208 participants without metabolic syndrome at baseline. Results: For 15 years, the incidence rate of metabolic syndrome (per 10, 000 person-years) varied by race and sex, with the highest rate in black women (279.2), followed by white men (241.9), black men (204.4), and white women (125.3). Depressive symptoms (per standard deviation higher) were associated with incident metabolic syndrome in white men (hazard ratio = 1.25, 95% confidence interval = 1.08–1.45) and white women (hazard ratio = 1.17, 95% confidence interval = 1.00–1.37) after adjustment for demographic characteristics and health behaviors. There was no significant association between depression and metabolic syndrome among black men or black women. Conclusions: Higher depressive symptoms contribute modestly to the onset of metabolic syndrome among white adults. Abstract : Supplemental digital content is available in the text.